On the Strategy for Implementing Economic Reform in the USSR - Makarov, Valery (American Economic Review, 1988)
The economic reform under way in the USSR is part of a general process of perestroika (restructuring), encompassing all spheres of social life. Consequently, the reform measures discussed below should be understood and analyzed in the wider context of that general process. Nevertheless, I will only be able to focus here on those parts of perestroika directly concerning the economy. Our reform strategy can be divided into three phases. Phase I (1985-87) has focused on the understanding of the past and the development of a strategy. Phase II (1988-90) will be a transitional phase during which the new system will be introduced, while many features of the old system will linger. Phase III (1991-95) will be the first full five-year plan period in which the entire system will be in place and functioning.